The Trope of Journey in Kavita Kane’s Ahalya’s Awakening: A Psychoanalytic Study - Joy, Divya; Pai , Geetha R. (International Journal of Psychosocial Rehabilitation, 2020)
Human life is a journey brimmed with lessons, adversities, joys, celebrations and special moments that will eventually guide us to our destination. Journeys are one of the utmost prevailing and accurate outfits for building renovations since they make evident our core yearnings in the outer world. Psychoanalytic criticism employs psychological principles to reconnoiter literature by laying prominence on either the psyche of the writer or of fantastic characters. The present paper will carry out a meticulous exploration of the psychological peregrination of Ahalya in Kavita Kane’s novel Ahalya’s Awakening, which is a reiterating of a eminent folklore revealed in Ramayana from the outlook of Psychoanalytic Criticism. The paper centers on probing how Ahalya voyages from a ratheripe kid, to an erudite and cloistered princess, to the amorous spouse of Rishi Gautam, grounded on Erik Erikson’s Psychosocial Theory of Human Development.